A Review of Multi-criteria Decision-Making Methods Using Application of Variable Weight Theory and IF-TOPSIS-EF - Ayasrah, Omar; Faiz, Mohd Turan (Springer, 2021)
The importance of the multi-criteria decision-making field is reflected by the high number of related researches mainly in the last decade. Even though, this field still has challenges that require attention from researchers in future studies. Most of multi-criteria decision-making studies either have not considered determining decision maker’s weights or applied subjective methods to derive these weights. Also, the absence of implementing sensitivity analysis to the decision maker’s weights is noticed. Furthermore, there is a need to develop new methods that utilizing the web or mobile technologies to deal with complexity and uncertainty adhered to multi-criteria decision-making problems. This paper represents the methodology to conduct a research that aims to combine two methods (IFS-TOPSIS-exponential based and Variable Weight Theory) in a new technique that tackles the abovementioned gaps by following induction research approach to validate the new technique by utilizing the secondary data, then to use interviews to develop the mobile application algorithm to perform solving MCDM problems virtually.